Relation-Specific Creative Performance in Voluntary Collaborations: A Micro-Foundation for Competitive Advantage? - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2011)
A fundamental question in the strategy literature is how sustainable competitive advantage can be generated within one firm and yet difficult to copy by another. We offer one solution to this conundrum by way of relation-specific performance that is developed in creative projects – where the individuals involved have significant latitude on the intended objectives as well as their collaborators on these projects. Because higher-level cognition is involved in navigating such projects from conception to implementation, there is heightened relation-specificity in their performance – as measured by how widely they are adopted by third-party users. This relationspecificity means that any performance improvement as a result of repeated collaborative efforts of a group of individuals is difficult to emulate or sustain outside of this specific group. This thus offers one way to simultaneously address several important critiques of the resource-based view of the firm. We rely on a novel set of data on user-written Facebook applications to demonstrate the relation-specificity of creative performance.